STRUKTUR CERITA DAN NILAI PENDIDIKAN CERITA RAKYAT DI KABUPATEN KEBUMEN SEBAGAI MATERI AJAR SASTRA DI SEKOLAH MENENGAH PERTAMA - Sari, Eprini Endah; Andayani, Andayani; Setiawan, Budhi (Universitas Sebelas Maret, 2018)
This research aims to describe: (1) contained structure in Kebumen folklore; (2)Â the educational value found in Kebumen folklore; (3) the relevance of educational value on Kebumen folklore with literary learning materials in junior high school. This research includes qualitative research using case study (observation and interview) and analyzing several documents in the object form of folklore study in Kebumen regency related with interview result with resource persons related to folklore, and result of interview with teacher and student. Data analysis techniques using interactive model analysis techniques namely data reduction, presentation, and withdrawal of conclusions or verification.The results of this research are: (1) the story structure that contained in the three folklore in Kebumen Regency includes (a) themes, (b) characters and characterization, (c) background, (d) plot, and (e)the message of the story; (2) the educational values that contained in three Kebumen Regency folklore include (a) the value of social education, (b) the value of moral education, (c) the value of religious education, (d) the value of custom/traditional education, and (e) the value of heroic education; (3) the relevance of educational value to folklore with literary learning materials in junior high school according to the criteria of Basic Competence and Keynote Competence and contains a moral value in it.